(How) Does Affect Influence the Formation of Habits in Exercise? - Weyland, Susanne; Finne, Emily; Krell-Roesch, Janina; Jekauc, Darko (Frontiers in Psychology, 2020)
Objectives: Habitually instigated exercise is thought to increase health behavior maintenance. Previous research has explored several aspects of habit formation. However, there is a lack of longitudinal research investigating affective determinants, especially post-exercise affective states. Therefore, the present study aimed to investigate a) if behavior frequency will enhance automaticity, b) if positive affect will enhance automaticity, and c) if positive affect will moderate the relationship between behavior frequency and automaticity. Methods: 226 participants (64% females, mean age 24 years) who attended weekly sports and gym classes at two universities were followed for 13 weeks. Class attendance was documented on a weekly basis (behavior frequency) during the semester. Before, during and immediately after each class, participants filled in the Feeling Scale (affective valence). Furthermore, at the beginning of each class, they answered a question about their automaticity in arriving at the decision to attend the class (instigation habit). We used a two-level modeling approach to predict subsequent automaticity by the different constructs at the previous attendance. Results: The cumulative frequency of prior class attendance did not significantly enhance the automaticity of the decision to re-attend the class. There were significant effects of valence on automaticity on the between-subject level, i.e., a one-point higher mean valence score was associated with a 0.62 point increase in automaticity (p=.001). No moderation effects of affect on the association between behavior frequency and automaticity were observed. Conclusions: Behavior repetition, albeit not significant, and positive affective states at the end of an exercise class may be beneficial in building exercise instigation habits. Practitioners and researchers alike may thus want to emphasize the importance of behavior repetition and affective response for health behavior maintenance.